An approach to the “Amicus Curiae” in Investment Arbitration - Espinoza Quiñonez, Sandro (2025)
Through this research, the authors offer an approach to the institution of the amicus curiae in investment arbitration. For this purpose, they explain its origins in order to understand its nature and operational logic in the abstract. Then, in concrete contrast with some emblematic cases, they explain the reasons that have justified their use, as well as the criteria for their acceptance and intervention as participants in investmentarbitration.